Enteric methane research and mitigation strategies for pastoral-based beef cattle production systems - Smith, Paul E.; Kelly, Alan K.; Kenny, David A.; Waters, Sinéad M. (Frontiers in Veterinary Science, 2022)
Ruminant livestock play key role in global society, through the conversion of lignocellulolytic plant matter into high quality sources of protein for human consumption. However as a consequence of the digestive physiology of ruminant species, methane (CH4) originating as a by-product of enteric fermentation is accountable for 40% of global agriculture’s carbon footprint and ~6% of global greenhouse gas (GHG) emissions. Therefore meeting the increasing demand for animal protein associated with a growing global population, whilst reducing the GHG intensity of ruminant production, will be a challenge for both the livestock industry and research community. Over recent decades, numerous strategies have been identified as having the potential to reduce the methanogenic output of livestock. Dietary supplementation with antimethanogenic compounds targeting members of the rumen methanogen community and/or suppressing the availability of methanogenesis substrates (mainly H2 and CO2), may have potential to reduce the methanogenic output of housed livestock. However, reducing the environmental impact of pasture based beef cattle will be a challenge, but may be achieved by enhancing the nutritional quality of grazed forage, in an effort to improve animal growth rates and ultimately reduce lifetime emissions. In addition, the genetic selection of low CH4 emitting and/or faster growing animals will likely benefit all beef cattle production systems by reducing the methanogenic potential of future generations of livestock. Similarly, the development of other mitigation technologies requiring minimal intervention and labour for their application, such as anti-methanogen vaccines, would likely appeal to livestock producers, with high uptake amongst farmers if proven effective. Therefore it is the objective of this review is to give a detailed overview of the CH4 mitigation solutions, both currently available and under development, for temperate pasture based beef cattle production systems. A description of ruminal methanogenesis and the technologies used to estimate enteric emissions at pasture is also presented.